Honorable Mentions - Panayides, Omiros (My University, 2026)
Honorable Mention at the 6th Emirates International Poster Festival (EIPF) https://drive.google.com/file/d/1QNJp7RcBxUq2ue-0Fw7OgKpKBt4OkMGQ/view?fbclid=IwZXh0bgNhZW0CMTEAAR2ds9H08xEs7u_GcFhnr3EgwJYKPjjZXkMjGc1x2G10N1gGN2bjI8VC6k8_aem_ew1Rl2ofPz0tbfrK1v1Prg
Keywords: Arts and entertainment